Z prac nad edycją Diariusza legationis JWJMci Pana Strażnika Wielkiego Koronnego odprawionej roku 1732 - Rzepka, Michał (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
In this article, the author merely indicates the selected results of the work on the edition of Diariusz legationis JWJMci Pana Strażnika Wielkiego Koronnego odprawionej roku 1732 (The diary of the 1732 diplomatic journey of Crown Great Guard) kept in the archives of Adam Mickiewicz University Library in Poznań. The research carried out in order to prepare the editorial work presented in this article was focused on the authenticity, source and the author of the text. The analysed diary is a late-eighteenthor early-nineteenth-century copy of an earlier version made between 1744 and 1826 – which is when it was acquired for the library of Czerniejewo-Radomice owned by the Skórzewski Counts. It was dated as a result of research that covered such issues as the paper it was written on, the watermarks in it and the entries describing its origin. The copy was made in a manor, most likely in Waplewo Wielkie owned by the Sierakowski family of the Ogończyk coat of arms. It has been determined that apart from the copy kept in the University Library in Poznań and a related record of the diplomatic journey published in Kuryer Polski (Polish Courier) from 1732 to 1733, there were at least two versions of the text: a diary included in the collection of Waplewo library and the original it was a copy of, which could be both the diary and additional documents and letters related to the diplomatic journey.